2015
DOI: 10.1111/hepr.12511
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based clinical practice guidelines for nonalcoholic fatty liver disease/nonalcoholic steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently the most common cause of chronic liver disease in industrialized countries worldwide, and has become a serious public health issue not only in Western countries but also in many Asian countries including Japan. Within the wide spectrum of NAFLD, nonalcoholic steatohepatitis (NASH) is a progressive form of disease, which often develops into liver cirrhosis and increases the risk of hepatocellular carcinoma. In turn, a large proportion of NAFLD/NASH is the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
192
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(203 citation statements)
references
References 138 publications
(274 reference statements)
5
192
1
5
Order By: Relevance
“…As expected, abnormal liver function test results were significantly related to NASH in this study, as has been reported previously [13,16,18]. There has been intense interest in the development of biochemical markers and scoring systems for predicting NASH and fibrosis [34]. To predict NASH, scoring systems including the hypertension, ALT, and insulin resistance (HAIR) score [6], Palekar's score [35], the Nash test [36], Gholam's score [37], the NASH clinical scoring system [38], the Nice model [39], and the NAFIC score [40] have been reported.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, abnormal liver function test results were significantly related to NASH in this study, as has been reported previously [13,16,18]. There has been intense interest in the development of biochemical markers and scoring systems for predicting NASH and fibrosis [34]. To predict NASH, scoring systems including the hypertension, ALT, and insulin resistance (HAIR) score [6], Palekar's score [35], the Nash test [36], Gholam's score [37], the NASH clinical scoring system [38], the Nice model [39], and the NAFIC score [40] have been reported.…”
Section: Discussionsupporting
confidence: 90%
“…NAFL is defined as the presence of hepatic steatosis without hepatocellular injury, whereas NASH is characterized by NAFL with hepatocellular ballooning injury with or without fibrosis. [1] NAFLD is now the most common cause of chronic liver disease worldwide [2] and affects 15% to 30% of the general population but is more prevalent (about 50%–90%) in patients with diabetes, metabolic syndrome, and severe obesity. [ 1 3 ] Current evidence suggests that 68% of adults in the United States are overweight, estimating that 75 to 100 million individuals may have NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-oxidant vitamin E and the insulin sensitizer pioglitazone are reported to be effective against NAFLD, but their long-term safety, especially for pioglitazone, are not well understood (5,6). Although clinical trials of several new drugs, including farnesoid X receptor agonist and PPARα/δ agonist, are ongoing (7,8), there is no curative drug treatment for NAFLD at present.…”
Section: Introductionmentioning
confidence: 99%